Interpreting Symbols and Philosophy in Papuan Wooden Sculptures (Asmat Carving Art) - Arifka, Ayu (Journal of Studies on Art, Culture and Society, 2025)
Asmat carving is one of Papua's cultural heritages that is rich in meaning and philosophical value. This article aims to explore and analyze the symbols and philosophies contained in Papuan wooden sculptures, especially Asmat carved artworks. Through an ethnographic approach and semiotic analysis, this research explores the meaning behind the motifs, forms, and techniques of making Asmat wooden sculptures. Data were obtained through direct observation, in-depth interviews with Asmat carvers, and study of related literature. The results show that Asmat wooden sculptures not only function as aesthetic artifacts, but also as a medium to represent the cosmology, spirituality and social values of the Asmat people. Motifs such as ancestors, totem animals and natural elements reflect the close relationship between Asmat people and the natural and spiritual world. Intricate carving techniques and the use of natural materials reflect local wisdom in utilizing natural resources sustainably. Furthermore, the sculpture-making process, which involves certain rituals and taboos, reveals the sacred dimension of this carving art. This research contributes to a deeper understanding of Papua's rich culture and the importance of preserving traditional arts in the context of modernization. The findings also highlight the potential of Asmat carving as a source of inspiration for the development of contemporary art and local wisdom-based creative industries.